Pain Pleasure Principle in Joy Harjo's Poetry: The Foundation of Personal Choices and Identity - Glayl, Mohanad Ghanim (Journal of English Language Teaching, Literature and Culture, 2024)
This article examines Joy Harjo’ journey, the renowned poet and musician, has navigated a tumultuous life filled with pain and adversity. The pain pleasure principle is a fundamental aspect of human decision-making. Beliefs, values, actions, and decisions are all shaped by this principle, but it is crucial to examine them critically through a postcolonial lens to better understand the power dynamics and social structures that influence our interpretation of pain and pleasure. A lot of studies have been conducted on Indigenous literature, but very little has delved into the exploration of pain and pleasure, specifically in the works of Joy Harjo. However, the current study argues that when examining Indigenous literature, it is essential to approach it through the lens of post-colonial theory and consider concepts such as identity, hegemony, and hybridity in order to fully understand the hidden motives behind these literary works. In her literature, Harjo's poetry serves as a testament to the transformative nature of language and its ability to heal. Harjo's work, particularly her book "Conflict Resolution for Holy Beings," emphasizes the importance of language in bridging cultural and linguistic gaps. Joy Harjo ‘literature reflects the pleasure serves as a driving force in our lives, motivating us to make certain choices and take specific actions. These choices and actions, in turn, shape our individuality and help us develop a unique identity. The study stresses on Pain pleasure principle that plays a crucial role in Indian American literature, particularly evident in the works of Joy Harjo